(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The objective of this study is to explain the role of credit policies in agricultural development of Iraq during the period 1979-1989 which were represented by the policy of co-operative agricultural bank the organization that responsible to finance agricultural sector for various reasons. It has been shown that there was no clear credit policy existed during the period concerned due to the differences between loans from year. The loan growth rate was low in general comparing with objectives of the agricultural development plans, a low production rates comparing with loans paid, the growth rate of average number of trees in each donum and the growth rate of livestock number was also low.In conclusion there should be a clear plan for credit within the agricultural economic plan, and the loans ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــ * بحث قدم الى المؤتمر العلمي الثامن لجمعية الاقتصاديين العراقيين / تحت شعار :السياسات الاقتصادية في العراق في ظل الحصار الاقتصادي والافاق المستقبلية 00 17- 19 اذار 1993 presented must be increased for the various agricultural activities which means that the co-operative agricultural bank should have more capital in order to increase its ability for presenting more loans.